Instructional media resources utilization of the Basic Education Department Faculty members at La Concepcion College's School Library and Media Center - Magpantay, Francisco F., Jr.; Golfo, Mary Grace P. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2013)
The research sought to understand the instructional media resources (IMR) utilization patterns of the faculty members of the Basic Education Department (BED) of La Concepcion College at the School's Library and Media center by gathering specific variables from the teachers and the staff in the library. External variable such as the library's compliance to the DepEd Order 56, series 2011 and Internal variables such as teachers' demographic profiles professional profiles, instructional media awareness, instructional media preferences and utilization were gathered and tested for associations.
The Cramer's coefficient values show moderate associations between instructional media utilization to age, educational attainment and years of teaching experience. Results also show that teachers prefer to use computers most often in their teaching. In contrast to the actual levels of utilization where from 1 to 5 scale, with 5 being the most utilized, print materials have the highest scale of 3.88, followed by non-print with 3 and the least utilized are computer collection with 2.88.
The research recommended that LCC-SLMC's collection should comply with minimum standards set by the DepEd Order 56, series of 2011. Moreover it is recommended that additional library promotion and services regarding the available instructional media in the library should be observed. Lastly, additional training for teachers regarding instructional media utilization should be done, specifically ICT integration into teaching.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: La Concepcion College School Library and Media Center; La Concepcion College Basic Education Department -- Faculty; Nonbook materials -- Philipines -- Bulacan -- Use studies